KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN YANG BERPRESTASI DALAM PENYELENGGARAAN SEKOLAH EFEKTIF - SUSAN FEBRIANTINA (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to gain a deep understanding of an achiever woman-principal leadership in implementing an effective school at SMAN 3 Depok from May to September 2012. This research is a qualitative case study method therefore it can find deep meaning. The credibility of the data obtained through extension of time doing research, finding of cycle in common data, persistence of researcher, triangulation, peer debriefing, finding for adequacy of references, and making detailed narration. This study concluded that (1) the combination of both interactive style and transformational style within motherly approach became a new model of principal leadership style in motivating subordinate, making decision and solving the problems; (2) leadership skills included technique, human interpersonal, and conceptual skill are important basic competences of the achievers principal leadership.